OPTIMALISASI PENDIDIKAN KESEHATAN DENGAN PEMBERIAN IMPLEMENTASI KEPERAWATAN TERHADAP PENCEGAHAN DIARE PADA KALANGAN REMAJA - Syavina, Putri; Nurhayati, Tanti Intan; Wijdaningtyas, Natasya; Wati, Putri Syalistia; Nurmalasari, Hernayanti; Sugandi, Trisha Kania; D, Dewi (LPPM UNINUS, 2024)
Diarrhea is one of the most prevalent gastrointestinal infection health problems globally, including in Indonesia. The total number of diarrhea cases in all age groups is 8.6%, in children under five 12.3%, and in infants 10.6% (Riskesdas, 2018). To reduce the number of deaths from this disease, diarrhea needs to be treated appropriately and immediately. One of the non-pharmacological treatments for diarrhea includes rehydration with oral rehydration saline solution (ORS), avoiding spicy, sour, and coconutty foods, eating little but often, giving zinc preparations, and selective antibiotics. The purpose of implementing this health education is to increase knowledge and understanding of diarrheal disease so that all students can respond properly if a case of diarrhea occurs. The methods used in health education are lectures and discussions. The results of this study showed a significant difference with a significance value (2-tailed) of 0.000 <0.05 between the pre-test and post-test results. This shows that there is a significant effect on the pre-test and post-test results regarding diarrhea material and prevention methods regarding consuming ORS, doing daily activities given. It can be concluded from the provision of health education to students of SMA Negeri 2 Cimalaka there is an increase in knowledge about diarrhea.